2021
DOI: 10.1111/1348-0421.12936
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of β‐hemolysins produced by the human opportunistic streptococci

Abstract: The genus Streptococcus infects a broad range of hosts, including humans. Some species, such as S. pyogenes, S. agalactiae, S. pneumoniae, and S. mutans, are recognized as the major human pathogens, and their pathogenicity toward humans has been investigated. However, many of other streptococcal species have been recognized as opportunistic pathogens in humans, and their clinical importance has been underestimated. In our previous study, the Anginosus group streptococci (AGS) and Mitis group streptococci (MGS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 135 publications
(172 reference statements)
0
11
0
Order By: Relevance
“…Oral mitis group streptococci are close relatives of pathogenic S. pneumoniae; however, they do not produce some pneumococcal virulence factors, such as cytotoxin (pneumolysin). 5,21 Thus, some pneumococcal virulence factors might not be necessary to infect or colonize in the oral cavity. By contrast, almost all oral streptococci produce GTFs, suggesting that GTFs and their glucan products provide an advantage in inhabiting the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral mitis group streptococci are close relatives of pathogenic S. pneumoniae; however, they do not produce some pneumococcal virulence factors, such as cytotoxin (pneumolysin). 5,21 Thus, some pneumococcal virulence factors might not be necessary to infect or colonize in the oral cavity. By contrast, almost all oral streptococci produce GTFs, suggesting that GTFs and their glucan products provide an advantage in inhabiting the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…4,[7][8][9][10] The number of members in the mitis group is increasing, and at present, more than 20 species have been reported. 5,[10][11][12][13] As the characteristics of the newly reported species have not been established yet, [11][12][13] this review will mainly summarize studies on three species, namely, S. oralis, S. sanguinis, and S. gordonii.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ILY is important for the pathogenicity of S. intermedius in humans [ 36 ]. In addition, investigations on the pathogenicity of other opportunistic streptococci that inhabit the oral cavity of humans revealed that a group of S. mitis strains displayed obvious β-hemolysis on blood agar [ 37 ]. The first reported β-hemolytic factor produced by S. mitis , mitilysin (MLY), is a typical CDC composed of four domains with extensive homology to pneumolysin (PLY) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumolysin (PLY), a cholesterol-dependent cytolysin, is a virulence factor of S. pneumoniae that is released from cells via autolysis [ 4 , 5 ]. PLY is found in virtually all pneumococcal isolates and plays a key role in bacterial colonization, invasion, and inflammation [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%